Implementation of Accountability in Village Fund Management: Systematic Literature Review - Abdallah, Zachari; Rahayu, Sri; Yudi, Yudi; Herawaty, Netty (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of the Village Fund is to enhance the village government's structure so that it may better manage growth and provide community services. in accordance with its authority, and to enhance the capacity of the community institutions in the village to plan, implement, and actively supervise development according to the village's potential. The study uses a systematic literature review approach by collecting data from a variety of sources, such as scholarly journals, official documents, and other pertinent publications. The results show that accountability in the management of village funds still faces various problems, such as low transparency, corruption, and restricted public participation. The search found ten articles in the indexed journal Scopus. Most research finds a link between the application of accountability in village fund management, while some studies find that there are major challenges related to accounting and the impact of local culture on management.